Indonesian Children Protection against Commercial Sexual Exploitation through Siri Marriage Practices in Maqashid Al-Shariah Perspective - Disemadi, Hari Sutra; Al-Fatih, Sholahuddin; Yusro, Mochammad Abizar (Faculty of Law, Universitas Brawijaya, 2020)
In Indonesia, the development of the mode of commercial sexual exploitation of children has been carried out through the practice of siri marriage. Children who are vulnerable to sexual exploitation due to lack of literacy in children, economic conditions of the family, and because of the environment and social status. The study aims to examine the protection of children against commercial sexual exploitation through the siri marriage mode from the Maqashid Al-Shariah perspective. This research uses normative juridical research methods with the statutory approach and conceptual approach. This research shows that siri marriage based on Islamic law is permissible if it meets the requirements of marriage, but based on Indonesian national law, siri marriage is prohibited if the purpose is to obtain material benefits for parents or the party to marry off children at an early age. Siri marriage can be used as a criminal offense if done against a child. Whereas in the Maqashid Al-Shariah perspective, marriage with children through siri marriage is legal or permissible. However, the marriage will only produce part of the purpose of marriage, while other objectives in perspective Maqashid Al-Sharia tend to be ignored because early marriage is prone to psychological problems and lack of skills in the family. As a result, marriage is considered to have the risk of giving birth to a bad thing in the family which can reduce the noble values which are the main mission of Islam.